2003
DOI: 10.1111/1541-1338.d01-5
|View full text |Cite
|
Sign up to set email alerts
|

European Gender Mainstreaming: Promises and Pitfalls of Transformative Policy1

Abstract: Gender mainstreaming requires a radical redefinition of policy values and practices. This initial discussion explores the way the mainstreaming approach attempts to change the definitions of the situation so that equality in gender relations becomes an element at the point of departure. Factors that may affect whether gender mainstreaming will become an institutional innovation include the extent to which there is a commitment to a gender mission, the level of sophistication in terms of gender and policy issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 12 publications
0
75
0
7
Order By: Relevance
“…In spite of these problems, gender mainstreaming could be attractive to feminist social movement actors because it presents a unique opportunity to move women's issues out of the policy ghetto and offers an innovative and potentially revolutionary new model for gender relations (Woodward 2003). In their analysis of gender mainstreaming diffusion in 157 countries, Jacqui True and Michael Mintrom (2001) find that feminist transnational advocacy networks involving femocrats and international nongovernmental organizations (INGOs) play a key role in the dissemination and implementation of gender mainstreaming.…”
Section: Understanding Gender Mainstreamingmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these problems, gender mainstreaming could be attractive to feminist social movement actors because it presents a unique opportunity to move women's issues out of the policy ghetto and offers an innovative and potentially revolutionary new model for gender relations (Woodward 2003). In their analysis of gender mainstreaming diffusion in 157 countries, Jacqui True and Michael Mintrom (2001) find that feminist transnational advocacy networks involving femocrats and international nongovernmental organizations (INGOs) play a key role in the dissemination and implementation of gender mainstreaming.…”
Section: Understanding Gender Mainstreamingmentioning
confidence: 99%
“…Up to now, the scholarship has focused on national-level analyses (Beveridge, Nott, and Stephen 2000;Booth and Bennett 2002;Squires 2005;Verloo 2001;Walby 2005;Woodward 2003) and on comparative analyses of national-level implementation (Daly 2005;True and Mintrom 2001;Woodward 2003). Although such efforts provide valuable insight into the policy diffusion process at the national level and the importance of feminist transnational networks in that diffusion process (True and Mintrom 2001), these accounts do not explain local-level factors that influence the adoption of gender mainstreaming among local feminist movements.…”
Section: Introductionmentioning
confidence: 99%
“…To this might also be added the close relationship between some of the research carried out and researchers in the area and the development of gender mainstreaming practices and practitioners in the field, such as in the realm of the experts' groups of the Euro-pean Commission, Council of Europe and EIGE (the European Institute for Gender Equality). Research has also shown the importance of collaboration, such as in the example of the "velvet triangle" described by Woodward (2003), linking feminist bureaucrats, trusted academics and the women's movement in the development of gender mainstreaming (Woodward 2003). Many of the abovementioned issues, besides being concerns in research, are currently the subject of lively debate among policy makers who work with the day-to-day implementation of gender mainstreaming.…”
Section: Gender Mainstreaming: a Contested Conceptmentioning
confidence: 99%
“…Moreover, municipalities organize projects on gender equality, which primarily touch on matters related to female representation in decision making (cf. Woodward 2003). Local Development Agreements (LDAs), furthermore, have been implemented in Sweden to stimulate civic participation and incite the deeper and broader citizenship of both women and men.…”
Section: Sweden and Italy: Differentiated Perspectives On Gender Mainmentioning
confidence: 99%